Beyond Petra: Nabataean Cultic and Mortuary Practices and the Cultural Heritage of the Negev and Edom - Tebes, Juan Manuel (2020)
While it is well known that the Nabataeans adopted and modified foreign cultic and funerary practices, particularly from the Greco-Roman and Egyptian worlds, their origins and precedents lie in the cultural heritage of the southern arid margins of the Levant and northern Arabia. This paper will make a reassessment of the Nabataean cultic and mortuary practices as they can be seen in rural and desert sites outside Petra, analyzing them within the background of their antecedents in southern Transjordan and the Negev. Particular attention will be placed on the geographical distribution and evidences of re-visiting and re-use of extra-mural Nabataean shrines and burials, and Edomite archaizing features present in the temple of Khirbet et-Tannur.